Differences in echocardiography, blood pressure, stroke volume, maximal power and profile of genes related to cardiac hypertrophy in elite road cyclists - Janikowska, Grażyna; Żebrowska, Aleksandra; Kochańska-Dziurowicz, Aleksandra; Mazurek, Urszula (Advances in clinical and experimental medicine : official organ Wroclaw Medical University, 2017)
Regular and moderate exercise is beneficial for improving the efficiency of the heart, but high-intensity physical activity may result in cardiac changes. This study focuses on the identification of the differences in echocardiography and blood variables before exercise, as well as the genes associated with cardiac hypertrophy at rest and in response to graded exercise test. The study group was made up of 28 road cyclists. Echocardiographic parameters and blood pressure were measured before exercise tests (N = 28). Blood samples were collected at rest, at maximal exercise intensity in a graded bicycle test and after 15 min of recovery; afterwards, blood morphology was estimated and RNA was isolated. Analysis of the expression profile of genes was performed for randomly selected road cyclists using the microarray method. Echocardiographic results and blood parameters divided cyclists into two groups: with and without left ventricular hypertrophy (N = 14). Differences in the structure and function of the left ventricle cyclists with a similar level of training were observed (p < 0.05). Diastolic blood pressure and resting heart rate were significantly lower in subjects with left ventricular hypertrophy (p < 0.05). The myosin light chain 9 and interleukin-6 signal transducer gene expression were differentially regulated in cyclists with left ventricular hypertrophy compared to athletes with normal heart dimensions in response to intensive exercise. We have found differences in echocardiography parameters, blood pressure, stroke volume and maximal power in the cyclists examined. These studies indicate the benefits of the recommended echocardiography measurements for professional endurance-athletes. The graded exercise altered the myosin light chain 9 and interleukin-6 signal transducer gene expression in the peripheral blood of road cyclists has also been found.